Gas6 Inhibits Toll-Like Receptor-Mediated Inflammatory Pathways in Mouse Microglia via Axl and Mer - Gilchrist, Shannon E.; Goudarzi, Salman; Hafizi, Sassan (Frontiers in Cellular Neuroscience, 2020)
Background: Microglia are well known key regulators of neuroinflammation which feature in multiple neurodegenerative disorders. These cells survey the CNS and, under inflammatory conditions, become ‘activated’ through stimulation of toll-like receptors (TLRs), resulting in changes in morphology and production and release of cytokines. In the present study, we examined the roles of the related TAM receptors, Mer and Axl, and of their ligand, Gas6, in the regulation of microglial pro-inflammatory TNF-α production and microglial morphology. Methods: Primary cultures of murine microglia of wild-type, Mer-/- and Axl-/- backgrounds were stimulated by the TLR4 agonist, lipopolysaccharide (LPS) with or without pre-treatment with Gas6. Gene expression of TNF-α, Mer and Axl were examined using RT-qPCR and ELISA was used to measure TNF-α release from microglia. Immunofluorescence staining of β-actin and the microglial marker Iba1 were performed to reveal microglial morphological changes, with cellular characteristics (area, perimeter, Feret’s diameter, minimum Feret, roundness and aspect ratio) being quantified using ImageJ software. Results: Under basal conditions, TNF-α gene expression was significantly lower in Axl-/- microglia compared to wild-type cells. However, all microglial cultures robustly responded to LPS stimulation with upregulation of TNF-α expression to similar degrees. Furthermore, Mer receptor expression was less responsive to LPS stimulation when in Axl knockout cells. Presence of Gas6 consistently inhibited the LPS-induced upregulation of TNF-α in wild-type, Mer-/- and Axl-/- microglia. Moreover, Gas6 also inhibited LPS-induced changes in microglial area, perimeter length and cell roundness in wild-type cells. Conclusion: Gas6 is able to negatively regulate the microglial pro-inflammatory response to LPS as well as via stimulation of other TLRs, acting through either of the TAM receptors, Axl and Mer. This finding indicates an interaction between TLR and TAM receptor signalling pathways and reveals an anti-inflammatory role for the TAM ligand, Gas6, which could have therapeutic potential.